PENERAPAN MODEL EXPERIENTAL LEARNING TERHADAP KREATIVITAS DAN HASIL BELAJAR MATA PELAJARAN IPS TERPADU DI KELAS VIII SMP NEGERI 2 SIROMBU - Daeli, Charles Sanjaya; Lahagu, Arianto; Telaumbanua, Wahyutra Adilman; Harefa, Yearning (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The low level of student creativity and learning achievement in Integrated Social Studies among eighth-grade students at UPTD SMP Negeri 2 Sirombu is reflected in the percentage of mastery that has not reached the minimum standard and the limited active participation of students in the learning process. This study focuses on examining the effectiveness of implementing the Experiential Learning model in improving the quality of the learning process and outcomes. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages, involving 20 students as research subjects. The learning model was applied through the stages of concrete experience, reflective observation, abstract conceptualization, and active experimentation. Data were collected through observation sheets on learning implementation, student creativity observation sheets, documentation, and learning achievement tests. The data were analyzed descriptively using percentages and mean scores, with a minimum mastery criterion (MMC) of 70 and a success indicator of at least 80%. The findings revealed improvements across all indicators: the implementation of learning increased from 48.33% to 85.83%, student creativity from 43.74% to 85.70%, the average score from 74.28 to 79.90, and learning mastery from 65% to 90%. Therefore, the implementation of Experiential Learning proved effective in strengthening student engagement and academic achievement in Social Studies instruction. ABSTRAK Rendahnya kreativitas dan capaian hasil belajar siswa pada mata pelajaran IPS Terpadu di kelas VIII UPTD SMP Negeri 2 Sirombu ditunjukkan oleh persentase ketuntasan yang belum mencapai standar minimal serta kurangnya partisipasi aktif siswa dalam proses pembelajaran. Penelitian ini berfokus pada efektivitas penerapan model Experiential Learning dalam memperbaiki kualitas proses dan capaian pembelajaran. Penelitian menggunakan desain Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, masing-masing melalui tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi, dengan subjek sebanyak 20 siswa. Model pembelajaran diterapkan melalui tahapan pengalaman konkret, refleksi, konseptualisasi abstrak, dan eksperimen aktif. Data dikumpulkan melalui lembar observasi keterlaksanaan pembelajaran, lembar observasi kreativitas siswa, dokumentasi, serta tes hasil belajar, kemudian dianalisis secara deskriptif kuantitatif berdasarkan persentase dan nilai rata-rata dengan acuan KKM 70 dan indikator keberhasilan minimal 80%. Hasil penelitian menunjukkan adanya perbaikan pada seluruh indikator, yaitu keterlaksanaan pembelajaran meningkat dari 48,33% menjadi 85,83%, kreativitas siswa dari 43,74% menjadi 85,70%, rata-rata nilai dari 74,28 menjadi 79,90, serta ketuntasan belajar dari 65% menjadi 90%. Dengan demikian, penerapan Experiential Learning terbukti efektif dalam memperkuat keterlibatan siswa dan capaian akademik pada pembelajaran IPS.